2022
DOI: 10.1186/s12884-022-04716-w
|View full text |Cite
|
Sign up to set email alerts
|

Biological networks in gestational diabetes mellitus: insights into the mechanism of crosstalk between long non-coding RNA and N6-methyladenine modification

Abstract: Background Gestational diabetes mellitus (GDM) is one of the most common complications of pregnancy. The mechanism underlying the crosstalk between long non-coding RNAs (lncRNAs) and N6-methyladenine (m6A) modification in GDM remain unclear. Methods We generated a lncRNA-mediated competitive endogenous RNA (ceRNA) network using comprehensive data from the Gene Expression Omnibus database, published data, and our preliminary findings. m6A-related ln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“… 32 Furthermore, YTHDF3 levels were also found to be upregulated in the placentas of gestational diabetes mellitus (GDM), showing excellent classifying power for the GDM and control groups. 33 These findings indicate a critical role for the m6A readers YTHDF2 and YTHDF3 in the occurrence, progression, and prevention of DM, and could thus help to restore the damaged functions of DM-BMSCs to improve the success rate of implantation. However, the role of YTHDF2 and YTHDF3 in DM-BMSCs and their effects on the implant success rate require further exploration.…”
Section: Discussionmentioning
confidence: 79%
“… 32 Furthermore, YTHDF3 levels were also found to be upregulated in the placentas of gestational diabetes mellitus (GDM), showing excellent classifying power for the GDM and control groups. 33 These findings indicate a critical role for the m6A readers YTHDF2 and YTHDF3 in the occurrence, progression, and prevention of DM, and could thus help to restore the damaged functions of DM-BMSCs to improve the success rate of implantation. However, the role of YTHDF2 and YTHDF3 in DM-BMSCs and their effects on the implant success rate require further exploration.…”
Section: Discussionmentioning
confidence: 79%
“…Researches had shown that lncRNA do not represent transcriptional noise. which played an essential role in tumors (34)(35)(36)(37). For example, autophagy-related lncRNA characteristics could accurately forecast the prognosis of patients with Bladder Cancer (38).…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers performed high throughput sequencing and analyzed the data from GEO to explore the underlying mechanism of m 6 A in GDM. Du et al generated a lncRNA-mediated competitive endogenous RNA (ceRNA) network, and found that hub genes were mainly involved in fatty acid metabolism pathway, which play a role in the development and adverse outcomes of GDM ( Du et al, 2022a ). Other GDM-associated hormones were also enriched, such as thyroid hormone and oxytocin ( Du et al, 2022a ).…”
Section: Rna M 6 a In Great Obstetrical Syndromes ...mentioning
confidence: 99%
“…Du et al generated a lncRNA-mediated competitive endogenous RNA (ceRNA) network, and found that hub genes were mainly involved in fatty acid metabolism pathway, which play a role in the development and adverse outcomes of GDM ( Du et al, 2022a ). Other GDM-associated hormones were also enriched, such as thyroid hormone and oxytocin ( Du et al, 2022a ). In addition, m 6 A modified genes related to monocyte infiltration were also clinically important in GDM, including CD81, CFH, FABP5, GBP1 etc.…”
Section: Rna M 6 a In Great Obstetrical Syndromes ...mentioning
confidence: 99%